Development and Validation of Chinese Parental Involvement and Support Scale for Preschool Children - Yue, Yaping; Zhu, Xiangru; Zhang, Yisi; Ren, Wanyu (Frontiers in Psychology, 2022)
Abstract: The present study developed the Chinese Parental Involvement and Support Scale for Preschool Children (CPISSPC) to measure parental involvement and support for preschool children. In Study 1, we conducted a literature review, open-ended interviews, a theoretical analysis, and expert interviews to create an item bank (58 items). In Study 2, 447 parents completed the item bank. Following item and Exploratory Factor Analysis, 30 items were retained. In Study 3, five new items were added to the 30-item version of the CPISSPC. A separate sample of 471 parents completed the 35-item version of the CPISSPC. After Confirmatory Factor Analysis, a final 18-item version of the CPISSPC was created with four factors: psychological support, educational support, play support, and life support. Construct validity and internal reliability (Cronbach’s α = 0.88) were satisfactory. Study 4 evaluated concurrent validity (n = 318). CPISSPC scores significantly and positively correlated with perceived social support, marital gratification, and children’s self-efficacy. CPISSPC scores significantly and negatively correlated with parents’ levels of burnout and loneliness. The CPISSPC exhibits good psychometric properties and can be used as a tool to measure parental involvement and support for preschool children.